2020
DOI: 10.1001/jamaneurol.2020.0117
|View full text |Cite
|
Sign up to set email alerts
|

Association of Stress-Related Disorders With Subsequent Neurodegenerative Diseases

Abstract: The objective of this thesis was to investigate the relationship of personality and stress with subsequent risk of Parkinson's disease (PD). In Study I, we conducted a population-based cohort study using questionnaire data from the Swedish Twin Registry to explore whether the personality traits, neuroticism and introversion, were associated with later PD risk. We also explored the role of smoking as a mediator in the relationship between personality and PD. Both neuroticism and introversion were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 136 publications
1
53
0
1
Order By: Relevance
“…Neuroimaging studies showed that the neuro-anatomical correlates of PTSD are decreased volume of the hippocampus and anterior cingulate cortex which are target regions of neuropathology in AD, DLB, and FTD ( 27 ). On the other hand, there are emerging evidence of a higher risk to develop cognitive decline in patients with PTSD ( 15 ).We could here hypothesize that patients with mild to moderate level of dementia are at higher risk respect to healthy subjects to manifest a variety of anxiety-related symptoms triggered in response to isolations and restrains imposed by quarantine and that this condition may render these patients more vulnerable to the development of a PTSD-like symptomatology. This in turn might potentially worsen the trajectory of cognitive decline.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Neuroimaging studies showed that the neuro-anatomical correlates of PTSD are decreased volume of the hippocampus and anterior cingulate cortex which are target regions of neuropathology in AD, DLB, and FTD ( 27 ). On the other hand, there are emerging evidence of a higher risk to develop cognitive decline in patients with PTSD ( 15 ).We could here hypothesize that patients with mild to moderate level of dementia are at higher risk respect to healthy subjects to manifest a variety of anxiety-related symptoms triggered in response to isolations and restrains imposed by quarantine and that this condition may render these patients more vulnerable to the development of a PTSD-like symptomatology. This in turn might potentially worsen the trajectory of cognitive decline.…”
Section: Discussionmentioning
confidence: 89%
“…In turn, lack of activities and global cognitive and physical stimulation may cause delirium in individuals with dementia, contributing further to morbidity. There is also increase evidence that psychological symptoms due to stressor events can contribute to cognitive decline (15).…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that there may be an increased need for assessment of new patients in geriatric psychiatry settings as a result of the negative consequence of quarantine and social distancing measures. In fact, psychological symptoms due to stressor events can contribute to cognitive decline (20) and social isolation, reduced social network, and loneliness can lead to generalized anxiety and major depression disorders in older individuals (21)(22)(23). Further, during lockdown it is likely that many older persons reduced their physical activity levels (5), which may impair symptoms; for example, cardiorespiratory fitness is also associated with cognitive functioning in older persons (24).…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that the same people who experience psychiatric conditions when they are young experience age-associated physical diseases when they are older. 3 , 4 Excess risk of physical disease and mortality among individuals with mental disorders has been detected in data from community surveys and outpatient and inpatient hospital records 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 and in data across different countries 4 , 13 , 14 , 15 , 16 and socioeconomic strata. 17 , 18 These findings suggest that preventing mental disorders in youth might be associated with the prevention of physical diseases and disabilities in older adulthood.…”
Section: Introductionmentioning
confidence: 99%